2013
DOI: 10.1080/00224499.2013.776659
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerable but Aloof Versus Naughty and Nice: Contrasting the Presentation of Male and Female Nude Models inVivaandPlayboy

Abstract: The current research examined contested meanings of nudity by comparing images of nude men and women that appeared in Viva, a 1970s women's magazine founded with the intention of foregrounding male nudity, to corresponding issues of Playboy. A major difference was obtained between male models and Playboy Playmates regarding direction of gaze and nudity. Although gaze aversion is often interpreted as a sign of submission and direct gaze is seen as a dominance cue, men in Viva displayed a high level of gaze aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…23 Much theoretical work has critiqued Hefner's assertions that his Bunnies and Playmates were sexually liberated free agents. Research on representations of models in Playboy at the height of its popularity in the 1970s found that Playboy represented women "as versions of the 'girl next door' despite the dissonance created by the obvious fact that they were posing nude" 24 Although Playboy featured co-eds, "girl next door" types, and popular celebrities rather than porn stars, its pages represented anything but the average American woman. Like most consumer magazine content, Playboy sold men an aspirational version of women's beauty.…”
mentioning
confidence: 99%
“…23 Much theoretical work has critiqued Hefner's assertions that his Bunnies and Playmates were sexually liberated free agents. Research on representations of models in Playboy at the height of its popularity in the 1970s found that Playboy represented women "as versions of the 'girl next door' despite the dissonance created by the obvious fact that they were posing nude" 24 Although Playboy featured co-eds, "girl next door" types, and popular celebrities rather than porn stars, its pages represented anything but the average American woman. Like most consumer magazine content, Playboy sold men an aspirational version of women's beauty.…”
mentioning
confidence: 99%